(untitled) - Berman, G. N (Moscow, 1977)
This collection of problems is designed for students is studying mathe-matical analysis in higher technical educational instituations. Problems and exercises are systematically selected and arranaged in compliance with the major sections of the course in mathematical analysis.
Keywords: Toán giải tích,Mathematical analysis